Strategy Changes After Errors Improve Performance - Van der Borght, Liesbet; Desmet, Charlotte; Notebaert, Wim (Frontiers in Psychology, 2016)
The observation that performance does not improve following errors contradicts the traditional view on error monitoring (Fiehler, Ullsperger, & von Cramon, 2005; Notebaert & Verguts, 2011; Núñez Castellar, Kühn, Fias, & Notebaert, 2010). However, recent findings suggest that typical laboratory tasks provided us with a narrow window on error monitoring (Desmet et al., 2012; Jentzsch & Dudschig, 2009). In this study we investigated strategy-use after errors in a mental arithmetic task. In line with our hypothesis, this more complex task did show increased performance after errors. More specifically, switching to a different strategy after an error resulted in improved performance, while repeating the same strategy resulted in worse performance. These results show that in more ecological valid tasks, post-error behavioural improvement can be observed.